# c-453=-8c-3

## Simple and best practice solution for c-453=-8c-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for c-453=-8c-3 equation:

Simplifying
c + -453 = -8c + -3
Reorder the terms:
-453 + c = -8c + -3
Reorder the terms:
-453 + c = -3 + -8c
Solving
-453 + c = -3 + -8c
Solving for variable 'c'.
Move all terms containing c to the left, all other terms to the right.
Add '8c' to each side of the equation.
-453 + c + 8c = -3 + -8c + 8c
Combine like terms: c + 8c = 9c
-453 + 9c = -3 + -8c + 8c
Combine like terms: -8c + 8c = 0
-453 + 9c = -3 + 0
-453 + 9c = -3
Add '453' to each side of the equation.
-453 + 453 + 9c = -3 + 453
Combine like terms: -453 + 453 = 0
0 + 9c = -3 + 453
9c = -3 + 453
Combine like terms: -3 + 453 = 450
9c = 450
Divide each side by '9'.
c = 50
Simplifying
c = 50`